Dynamical model for nonleptonic decays of hyperons - Riazuddin; Fayyazuddin; Zimmerman, A. H. (American Physical Society (APS), 1965)
A dynamical model based on broken unitary symmetry is developed for nonleptonic decays of hyperons. The contributions to these decays are taken from the primary current-current interaction and from poles due to the baryons, the K meson, Y0*(1405), and the decuplet of baryon resonances (B10*). The contributions from the baryon and K-meson poles are calculated on the assumption that weak baryon-baryon and K-π transitions transform like divergences of the relevant weak currents, which are members of octets. The contributions from poles due to Y0* and the B10* resonances must be included to explain the p-wave amplitudes. Both s- and p-wave amplitudes then satisfy the triangular relations and fit the experimental values for the signs and magnitudes. The model predicts the correct sign of the K20-K10 mass difference. © 1965 The American Physical Society.